Analysis of Social Conflict and Social Change in The Nickel Boys Novel - Azizah, Wahyu Agustin (Journal of Literature, Linguistics, & Cultural Studies, 2023)
Social conflict is a common phenomenon in everyday life. Basically, social conflict occurs because of differences in interests between the two groups. As a result, this triggers the emergence of social change in society. Not only in real life but conflict can also be represented in literary works, such as in the novel The Nickel Boys by Colson Whitehead. The novel tells about the social conflicts that occurr in black and white US society, especially at the Nickel Academy. Furthermore, this study aims to determine the form and impact of social conflict on social change in the novel. This research is included in literary criticism, which uses the sociology of literature approach by applying Ralf Dahrendorf's conflict theory. The data in this study were taken from the novel The Nickel Boys by Colson Whitehead, which was published in 2019 by Doubleday, US. Research data were analyzed by identifying, classifying, interpreting, and making conclusions. This research resulted in two findings. First, the social conflict in the novel is represented through several acts of discrimination that occur at Nickel Academy. This social conflict occurred as a result of differences in interests and goals between groups in the social structure there, namely the Nickel Academy staff group, which has the above social structure (superordinate group) and the Nickel Academy student group, which has the lower social structure (subordinate group). Second, the social conflict that occurs in the novel has an impact on social change which is related to the social structure that exists in the Nickel Academy. This change is represented by the removal of the social structure that was there by the US government. Moreover, the researcher suggests future researchers use another approach, such as structuralism, psychology, or others. In addition, they can also use other conflict theories, such as the conflict theory of Karl Marx, Lewis A. Coser, or George Simmel.